2023
DOI: 10.1515/edu-2022-0197
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of GPA at Undergraduate Level using MLR and ANN at Arab International University During the Syrian Crisis: A Case Study

Abstract: The aim of the current study is to estimate the graduation grade point average (GPA) at the Arab International University (AIU). The importance of this study is that it is the first of its kind in Syria, particularly under the conditions of the bitter war, which has not yet come to its end. The sample of the study consists of data collected from AIU registry system, which covers students of six faculties from both sexes over a period of 5 years, i.e., between 2014 and 2018. The variables of the study include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Data from six faculties were gathered from the university's registration system, encompassing variables like high school GPA, source of student certificates, and student gender (GR). Utilizing Multiple Linear Regression (MLR) and Artificial Neural Network (ANN) methods, it was revealed that male students notably impact GPA, highlighting their significance as a pivotal factor in academic outcomes [12]. Another study focused on secondary students' academic data in mathematics, evaluating accuracy, precision, recall, and f-1 score.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from six faculties were gathered from the university's registration system, encompassing variables like high school GPA, source of student certificates, and student gender (GR). Utilizing Multiple Linear Regression (MLR) and Artificial Neural Network (ANN) methods, it was revealed that male students notably impact GPA, highlighting their significance as a pivotal factor in academic outcomes [12]. Another study focused on secondary students' academic data in mathematics, evaluating accuracy, precision, recall, and f-1 score.…”
Section: Related Researchmentioning
confidence: 99%
“…This research data was obtained through formal requests for information from the Informatics Postgraduate study program. The data submitted for research purposes comprises university data, the origin of the study program, undergraduate GPA, master's GPA, TOEFL scores, and the length of study [12]. In comparative analysis, this research aims to identify the relative influence of each variable on predicting student graduation.…”
Section: A Data Collectionmentioning
confidence: 99%